Photoconsortium - International Consortium for Photographic Heritage - (:unkn) unknown (My University, 2026)
PHOTOCONSORTIUM – International Consortium for Photographic Heritage is a non for profit association whose purpose is the promotion and enhancement of the culture of photography and photographic heritage. To achieve its statutory goals, PHOTOCONSORTIUM aims to promote, organize and manage conferences, exhibitions, awards and training courses as well as to carry out publishing activities. The association participates, and promotes the participation of its members, in new projects and initiatives also in collaboration with third parties, including but not limited to participation in the Programmes of the European Commission. All the initiatives of the association are primarily devoted to serving the interests of its members. PHOTOCONSORTIUM is the expert hub on photography for Europeana.eu and curates the photography collection.